FHR-5 Serum Levels and CFHR5 Genetic Variations in Patients With Immune Complex-Mediated Membranoproliferative Glomerulonephritis and C3-Glomerulopathy - Garam, Nóra; Cserhalmi, Marcell; Prohászka, Zoltán; Szilágyi, Ágnes; Veszeli, Nóra; Szabó, Edina; Uzonyi, Barbara; Iliás, Attila; Aigner, Christof; Schmidt, Alice; Gaggl, Martina; Sunder-Plassmann, Gere; et al. (Frontiers in Immunology, 2021)
Background: Factor H-related-5 (FHR-5) is a member of the complement Factor H protein family. Due to the homology to Factor H, the main complement regulator of the alternative pathway, it may also be implicated in pathomechanism of kidney diseases where Factor H and alternative pathway dysregulation play a role. Here, we report the first observational study on CFHR5 variations along with serum FHR-5 levels in immune-complex-mediated membranoproliferative glomerulonephritis (IC-MPGN) and C3 glomerulopathy (C3G) patients together with the clinical, genetic, complement and follow-up data. Methods: 120 patients with a histologically-proven diagnosis of IC-MPGN/C3G were enrolled in the study. FHR-5 serum levels were measured in ELISA, the CFHR5 gene was analyzed by Sanger-sequencing, and selected variants were studied as recombinant proteins in ELISA and SPR. Results: Eight exonic CFHR5 variations in 14 patients (12.6%) were observed. Serum FHR-5 levels were lower in patients compared to controls. Low serum FHR-5 concentration at presentation associated with better renal survival during the follow-up period, furthermore, it showed clear association with signs of complement overactivation and clinically meaningful clusters. Conclusions: Our observations raise the possibility that FHR-5 protein plays a fine-tuning role in the pathogenesis of IC-MPGN/C3G.